An autoimmunity-associated allele of PTPN22 enhances innate antiviral immunity to protect against acute coronavirus infection - Alec M. Bevis; Kathryn J. L. H. Rosa; Nancy Schwarting; Tammy R. Cockerham; Catherine M. Kerr; Sunil More; Anthony R. Fehr; Robin C. Orozco (Proceedings of the National Academy of Sciences, 2026)
Allelic variation can impact viral clearance and disease severity. Still, our understanding of the effect of the autoimmunity-associated allelic variant of Ptpn22 (PEP-R619W) on antiviral immunity remains incomplete, as previous reports have only focused on chronic lymphocytic choriomeningitis virus infection. This research defines how the loss of Ptpn22 (PEP-null) and PEP-R619W changes antiviral immunity during an acute coronavirus infection. We address the hypothesis that CRISPR/Cas9-generated PEP-null and PEP-R619W mice have enhanced antiviral immunity over PEP-wild-type (WT) mice during coronavirus infection. Following mouse hepatitis virus A59 infection, we interrogated pathology, cytokine production, and cellular responses in the blood, spleen, and liver of PEP-WT, PEP-null, and PEP-R619W mice. Key findings show that PEP-R619W mice have reduced viral titer and weight loss, increased survival, and more mature natural killer (NK) cells in the liver and spleen compared to PEP-WT mice. Interestingly, protection against disease in PEP-null mice was inoculation dose dependent, whereas PEP-R619W conferred immunity regardless of infection dose. Further, Rag1 −/− PEP-R619W mice had increased survival and reduced viral titer over Rag1 −/− PEP-WT mice. PEP-R619W mice also had higher concentrations of interferon-gamma (IFNγ) and enhanced IFNγ production by mature NK cells in the liver at 3 d postinfection. Finally, NK cell depletion elevated PEP-R619W viral titer to similar levels as PEP-WT mice. This study investigates the role of Ptpn22 within NK cells and demonstrates that the Ptpn22 allelic variant augments NK cell function and is beneficial during coronavirus infection.